Image preprocessing method for underground variable lighting conditions - SHANG Changchun; MA Hongwei; CHEN Yanbing (Gong-kuang zidonghua, 2014)
The paper introduced two histogram-based preprocessing algorithms and Gamma correction algorithm, proved that overall effect of histogram specification was better than histogram equalization by example comparing. It proposed a method only processing illumination component ratio of image, the method enhances contrast of image, and retains more detailed information than the image preprocessing method based on the whole image. The results of histogram specification and Gamma correction process to illumination component of image show that histogram specification gets the best results.